Depression and Its Relationship with Coping Strategies and Illness Perceptions during the COVID-19 Lockdown in Greece: A Cross-Sectional Survey of the Population. (26th August 2020) - Skapinakis, Petros; Bellos, Stefanos; Oikonomou, Achilleas; Dimitriadis, Georgios; Gkikas, Paschalis; Perdikari, Evridiki; Mavreas, Venetsanos
Abstract : Objective . The COVID-19 epidemic has shown a more benign course in Greece possibly due to the early lockdown measures. Mental health consequences of the lockdown however are unknown. In addition, illness perceptions and relevant strategies to cope with the stress of the epidemic may have played a role in complying with the restrictions. We conducted a survey of the Greek population with the aim to investigate the prevalence of anxiety and depression during the lockdown, the emotional impact of the epidemic, and the effect of coping strategies and illness perceptions in mental health. Methods . Adult persons were invited during the peak of the lockdown period through social media. Depressive and anxiety symptoms were assessed with the PHQ-9 and GAD-2 scales, respectively. Coping strategies were assessed with selected items of the Brief COPE questionnaire, while illness beliefs were assessed with items from the revised Illness Perception Questionnaire (IPQ-R). Results . A total of 3379 individuals took part. A strong emotional impact of the epidemic was more often in women and in those with severe financial difficulties. Levels of depressive and anxiety symptoms were high but similar to past assessments. Participants showed high levels of personal control and used more often positive strategies to cope with the stress of the epidemic. Depressive symptoms were higher in the younger, in students, in those with a stronger emotional impact, in those isolated due to symptoms, and those overexposed to media for COVID-19-related news. Lower levels of depression were seen in those using positive coping strategies and showing high levels of personal and treatment control. Conclusions . The study shows that certain psychological and social determinants were associated with increased depressive symptoms during the lockdown warranting the development of public health guidelines to mitigate the effects of the epidemic to the mental health of the population.